PARAMETER FISIS GUGUS GALAKSI ABELL 1190 - Fajriyatullah Hanif, Adam
Galaxy clusters are the most massive gravitational structures in the universe. Clusters of galaxies play a very important role in observational cosmology. Information about the evolution of large-scale structures can be obtained through observations of galaxy clusters. In this Final Project, the determination of the physical parameters of the Abell 1190 galaxy cluster will be carried out. The physical parameters to be determined are: distance, projection radius, members, and mass of the Abell 1190 galaxy cluster. In this Final Project, there are two methods used to determine the physical parameters of Abell 1190 galaxy cluster, namely the Bukhari and Color Cut. The Bukhari method is a method of determining members by iterating membership based on the radial velocity and the projection radius in the central area. Then enlarged by evaluating the value of ???????? and ???????? by 10% which must satisfy the new ???????? and ???????? which is less than the old ???????? and ????????, while the Color Cut method is a method of determining the members of a galaxy cluster based on the relationship of color and magnitude using the color slices ?????????,?????????, and ?????????. These color cut bin sizes for ?????????,?????????, and ????????? are 0.4,0.2, and 0.2. The use of these two different methods is expected to increase the accuracy in determining the physical parameters of the Abell 1190 galaxy cluster. After processing the data, it is found that the Abell 1190 galaxy cluster has a luminosity distance of 354.13 ????????????, a number of members as many as 100 galaxies, and a mass of 2.8 ???? 1014 M?.